2020
DOI: 10.3390/ma13020422
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Screening of the Structural and Thermomechanical Properties of FDM Filaments Comprising Thermoplastics Loaded with Cellulose, Carbon and Glass Fibers

Abstract: Additive manufacturing (AM) has been rapidly growing for a decade in both consumer and industrial products. Fused deposition modeling (FDM), one of the most widely used additive manufacturing methods, owes its popularity to cost effectiveness in material and equipment investment. Current efforts are aimed toward high load-bearing capacity at low material costs. However, the mechanical reliability of end-products derived from these compositions and their dependence on microstructural effects, have remained as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In Stage C, an integrated evaluation using a reliability-based approach is carried out using the calculations obtained in stages A and B. Since it is essential to predict reliability of end-products because this is one of their major limitations [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Stage C, an integrated evaluation using a reliability-based approach is carried out using the calculations obtained in stages A and B. Since it is essential to predict reliability of end-products because this is one of their major limitations [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, physical and mechanical properties of polymers have hindered their utilization due to inferior properties compared to conventional materials such as metals and alloys. Several studies reported improved mechanical properties of polymers through synthetic or natural fibers reinforcement [ 5 , 6 , 7 ]. However, 3DP of continuous fiber-reinforced polymer (CFRP) composites is still a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness properties of PLA-based composites are typically enhanced by adding different kind of fillers such as metal powder, carbon or glass-fibers, cellulose, microcellulose, wood and agro-fibers [ 23 , 24 ]. However, at the same time, tensile and impact strength properties are decreasing [ 23 , 25 , 26 , 27 , 28 ]. Also, due to quite low glass transition temperature, typically below 60 °C, the suitability of PLA-composite in many applications is limited.…”
Section: Introductionmentioning
confidence: 99%